The prevalence of germline pathogenic variants in Estonian colorectal cancer patients: results from routine clinical setting 2016–2021 - Roht, Laura; Tooming, Mikk; Rekker, Kadri; Roomere, Hanno; Toome, Kadri; Murumets, Ülle; Šamarina, Ustina; Õunap, Katrin; Kahre, Tiina (Frontiers in Genetics, 2022)
Background. Colorectal cancer (CRC) is the third most common cancer in Estonia in both women and men. According to the Estonian National Institute for Health Development, in 2017, there were 357 new colorectal cancer cases in women and 282 in men. In 2018, there were over 1.8 million new cases worldwide. The Mayo Clinic found in a prospective, two-year multi-site study of CRC patients that 15.5% of patients carried pathogenic germline variants (PGV), using an >80 gene Next Generation Sequencing (NGS) panel. Material and methods. This retrospective study aimed to analyse the estimated prevalence of pathogenic/likely pathogenic germline variants in Estonian colorectal cancer patients using NGS in a routine clinical setting. We gathered five-year data (July 2016-July 2021) of colorectal cancer patients (mostly not selected for age or family history) tested with either Illumina TruSight Cancer (94 genes) or TruSight Hereditary Cancer (113 genes) NGS panels. Results. Three hundred and fourteen NGS analyses were performed due to either CRC or polyposis in anamnesis and/or family anamnesis, including 126 CRC cases and 44 colorectal polyposis cases, while 144 were either healthy family members or had other types of cancers. While a known disease-causing variant was identified in 16.4% of all cancer patients tested, we found that 21.4% of CRC patients had such a variant. The genetic cause of colorectal polyposis was found in 25.0% of cases, most often affecting the gene MLH1; the second and third most affected genes were MSH2 and CHEK2. Other genes with disease-causing variants found in CRC patients included APC, BLM, BMPR1A, BRCA1, FANCM, MSH6, MUTYH, PMS2, PPM1D, SMAD4, SPINK1 and VHL. Conclusion. Our result give an overview of genetic testing of CRC patients, the prevalence of disease-causing variants and their landscape in Estonia. According to Estonian data, only 2.7-6.1% of CRC patients are genetically tested, which is around ten times less frequently than breast cancer patients and their family members. The diagnostic yield of CRC patients is 21.4%, suggesting that genetic testing will likely improve timely diagnosis and outcomes.